Infiltration function evaluation under border-strip irrigation conditions to Al-Khadra North East area in Libya. - Mumen , Mohamed A.; Ikhneifer, Ali A. (Al-Mukhtar Journal of Sciences, 2000)
This study was conducted to determine the behavior of the infiltration function along the growing season under border-strip irrigation conditions for clayey to clay loam textured soils of Al-Khadra Northeast area. The results showed that the soil infiltration characteristics have changed from one irrigation to another during the growing season. There was a decreasing effect due to the number of irrigations and an increasing effect due to the irrigation interval on the soil infiltration characteristics. Phillip’s equation (1957) was used to describe the soil infiltration characteristics and the Zero-Inertia model was used to simulate the infiltration characteristics. Best correlation coefficient was found between actual and predicted infiltration data in most cases. Consequently, two empirical formulas were developed, the first for the variable (k) in Phillip’s equation with soil moisture and number of irrigations along the season and the second for the variable (k) with irrigation interval and number of irrigations during the season.